2011
DOI: 10.1016/j.resp.2011.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter null male mouse pups have lower ventilation in air and 5% CO2 at postnatal ages P15 and P25

Abstract: In Wild Type (WT) and serotonin transporter (5HTT) null mice, we studied oxygen consumption, ventilation and heart rate in air and 5% CO2 at postnatal (P) days P5, P15, and P25 using either a head-out (younger mice) or whole body plethysmograph (older mice). Body weight and temperature did not differ between the groups. Oxygen consumption differed significantly only in females at P15 when it was reduced in 5HTT nulls (P < 0.01). Heart rate similarly differed only in female 5HTT nulls at P15 being decreased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Consistent with this conclusion is the observation that in serotonin-deficient mice, gasping is markedly attenuated during a short time window in postnatal development [44]. Additionally, recent studies in mice with genetic impairment to serotonergic neuromodulation have demonstrated that males are vulnerable to a loss of chemosensitive responsiveness [45] [46]. However, while both the failure to effectively gasp/autoresuscitate [11] and disturbances in serotonergic mechanisms [47] appear critical in the disease mechanisms of SIDS, other biological factors may also be involved with the etiology of SIDS.…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with this conclusion is the observation that in serotonin-deficient mice, gasping is markedly attenuated during a short time window in postnatal development [44]. Additionally, recent studies in mice with genetic impairment to serotonergic neuromodulation have demonstrated that males are vulnerable to a loss of chemosensitive responsiveness [45] [46]. However, while both the failure to effectively gasp/autoresuscitate [11] and disturbances in serotonergic mechanisms [47] appear critical in the disease mechanisms of SIDS, other biological factors may also be involved with the etiology of SIDS.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, in the absence of endogenous serotonin activation, gasping at the network level is abolished (Tryba et al, 2006). This finding has been confirmed in intact animals using several approaches aimed at depleting serotonergic neuromodulation within the brainstem (Li and Nattie, 2008; Cummings et al, 2009, 2011; Penatti et al, 2011). Specifically perinatal loss of brainstem serotonin neurons compromises the ability of rats to survive (Cummings et al, 2009, 2011).…”
Section: Sids and Central Cardio-respiratory Controlmentioning
confidence: 63%
“…In mice with disrupted serotonergic reuptake, hypercapnic chemosensitivity is disrupted as early as postnatal day (P) 15 (Penatti et al, 2011). Interestingly, this loss of chemosensitivity is biased toward the male gender (Li and Nattie, 2008; Penatti et al, 2011). Therefore, changes in the serotonergic network can potentially increase susceptibility to SIDS in both an age and gender dependent manner.…”
Section: The Influence Of Gender and Age Over Cardio-respiratory Fmentioning
confidence: 99%
“…The oxygen concentration in the chamber was measured using an electrochemical analyzer (Maxtec OM-25RME). The flows of oxygen and nitrogen were carefully regulated using flow meters (Cole-Palmer) to maintain a fresh O 2 gas flow rate 8 -10 times the calculated oxygen consumption of the litter and mother (59). Both mothers and pups tolerated this exposure well, as also reported by others (8,24).…”
Section: Methodsmentioning
confidence: 85%